Hubungan Motivasi Kerja dan Disiplin Kerja dengan Kinerja Pegawai di Dinas Pendidikan Kabupaten Mojokerto - Sigit Priyo Sembodo (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2020)
An organization of good governance should have the motivation of employees with high job of work and discipline. If employees work well in accordance with the ability and motivation work influenced by their skills and responsible for his job as a form of discipline work and an organization that will be able to more developed ease the achievement of the purpose of the organization. The purpose of this study are (1) the correlation between work motivation with employee performance, (2) the correlation between work discipline with employee performance, (3) the correlation between work motivation and work discipline with the performance of employees in educational department of mojokerto.A method in this research was used a quantitative approach. The techniques to take data collection here is closed questionnaires and Data processing techniques uses correlation product moment test and multiple correlation with the significant level of 5% to know is there any relationship between the variables or not. The result showed that (1) it is proved that there is correlation between work motivation and performance of employees with a correlation coefficient of 0.792, (2) there is a correlation between the work discipline with employee performance with a correlation coefficient of 0.981, (3) there is a correlation between work motivation and work discipline with the employee's performance with a correlation coefficient of 0.981. Based on the analysis of the data above it can be concluded that there are correlation between work motivation and work discipline with the employees performance in educational department of mojokerto.